Capacidad predictiva de las escalas de valoración en la prevención de ulceras por presión en adultos. - Barrientos Sulca, Sara (2018)
Objective: To systematize the available evidence on the predictive capacity of the valuation scales in the prevention of pressure ulcers in adults Material and method: Systematic observational and retrospective review, which synthesizes the results of multiple primary investigations. Essentials of evidence-based nursing for its rigorous methodology, identify relevant studies to answer specific clinical practice questions, search I consider full-text articles, and selected articles had a critical reading, using the grade system to assign the recommendation force. Results: In the definitive selection of articles of predictive capacity of assessment scales in the prevention of pressure ulcers in adults was the scale Braden had sensitivity: 41-100%, specificity: 21-92%, positive predictive value: 19-31 %, negative predictive value: 90-97%. Conclusions: 100% (13) of articles determined the predictive capacity of the valuation scales in the prevention of pressure ulcers in adults based on specificity, sensitivity, predictive value. Having the highest predictive capacity the Braden scale followed by Waterlow, ENMIA and Norton.